The Combination of Exposure‐Response and Case‐Control Analyses in Regulatory Decision Making. (24th January 2013) - Yang, Jun; Zhao, Hong; Garnett, Christine; Rahman, Atiqur; Gobburu, Jogarao V.; Pierce, William; Schechter, Genevieve; Summers, Jeffery; Keegan, Patricia; Booth, Brian; Wang, Yaning
Abstract To reduce the bias introduced by confounding risk factors, a case‐control comparison was incorporated in the exposure‐response (ER) analysis to evaluate the recommended dosing regimen for trastuzumab in a pivotal trial. Results of Kaplan‐Meier survival analysis suggest that patients with metastatic gastric cancer (mGC) in the lowest quartile trough concentrations of trastuzumab in cycle 1 (Cmin 1) had shorter overall survival (OS) than did those in other quartiles. The result of the case‐matched control comparison suggests that adjusting for these risk factors, patients with the lowest quartile of trastuzumab exposure did not benefit from addition of trastuzumab treatment to chemotherapy. The identified subgroup without survival benefit and the ER relationship support the recommendation on conducting clinical trials to identify a treatment regimen with greater exposure and acceptable safety profiles and to prospectively evaluate whether this treatment regimen will result in survival benefit for the identified subgroup.